Unusual Presentation of Mycobacterium abscessus Thigh Mass: A Case Report - Ryan J. Blake; Grant R. McChesney; H. James Williams; Steven M. Holland; Allison M. Lastinger (Case Reports in Infectious Diseases)
Mycobacterium abscessus is a rapidly growing non-tuberculous Mycobacterium (NTM) primarily associated with pulmonary infections, particularly in individuals with underlying lung conditions. While soft tissue infections are less common, their incidence has been increasing. These infections are challenging to treat due to inherent resistance to many antibiotics obtained through spontaneous mutation as well as physical characteristics of the microbes. The case presented here describes a 61-year-old female without obvious risk factors for mycobacterial infection who developed an intramuscular abscess over a 2-year period following a mechanical fall. Surgical resection with a complex antibiotic regimen was required based on macrolide resistance and a lack of established treatment plans for such a rare presentation. This case highlights the increasing incidence of NTM and the variable clinical presentation. Early identification with a combination of surgery and antibiotics is usually indicated to successfully manage these infections. Even without obvious risk factors, NTM infection should be considered in the presence of soft tissue and intramuscular abscesses.